Uma ferramentaWeb para simplificar mensagens de erro de programação para estudantes iniciantes - Resende, Valmir Vinicius da Cunha (2024)
The practice in computer science has been widely assisted by the use of Online Judges. They are applications that can be used to support source code development and programming logic practice. The Online Judge receives the submission of source code and executes it, subjecting it to each test case of the problem. If an error occurs, a message is returned to the student; however, these messages can be difficult to understand, increasing the student’s learning curve. Faced with this problem, the project developed in this work aims to convert these difficult-to-understand messages into simple messages. Since it is not possible to perform this conversion task for all online judges, The Huxley, as one of the most popular in the Brazilian academic community, was the focus of this work. To carry out the activities, studies were conducted on the API developed by Galileu Santos de Jesus (EME), Master in Computer Science from the Federal University of Sergipe (UFS), responsible for converting error messages into user-friendly messages, and on The Huxley’s API, in order to authenticate the user and access submissions. Thus, the developed application serves as a web interface to integrate the two environments, allowing student use. From there, software requirements were elicited to delimit its scope, enabling the continuation of the activities in this work. The development of the application resulted in a successful integration between the EME API and the TH API, enabling the conversion of complex error messages into easily understandable messages. The resulting web interface provides students with a simple usage experience to convert incorrect TH submission messages into a friendlier message.